MALDI–HRMS imaging and HPLC–HRESI–MSn characterisation of kaurane diterpenes in the fruits of Xylopia aethiopica (Dunal) A. Rich (Annonaceae). Issue 3 (24th December 2019) - Kyekyeku, James Oppong; Asare‐Nkansah, Samuel; Bekoe, Samuel Oppong; Sezgin, Selahaddin; Adosraku, Reimmel Kwame; Spiteller, Michael
Abstract: Introduction: Kaurane diterpenes, notably xylopic acid, have demonstrated important biological activities including analgesia, anti‐oxidant, antimicrobial and cytotoxicity. The fruits of Xylopia aethiopica have been reported to be a rich source of kaurane diterpenes. Objective: An analytical approach for detailed imaging and characterisation of selected kaurane diterpenes was developed using matrix‐assisted laser desorption/ionisation high‐resolution mass spectrometry (MALDI‐HRMS) imaging techniques and high‐performance liquid chromatography‐high resolution electrospray ionisation‐tandem mass spectrometry (HPLC‐HRESI‐MS n ) studies, respectively. Methods: The images of the compounds were constructed based on selected ions from their HRESI–MS spectra. The matrix employed comprised a solution of α–cyano–4–hydroxycinnamic acid (HCCA) in acetonitrile–water with trifluoroacetic acid (TFA). HPLC–HRESI–MS n measurements were conducted on an LTQ–Orbitrap spectrometer equipped with a heated electrospray ionisation (HESI)–II source. Results: The analytical strategy adopted showed the spatial distribution of the compounds in the fruits of X. aethiopica based on the dominant ions at m/z 301.2163 [M + H – HOCOCH3 ] + and m/z 399.1932 [M + K] + for xylopic acid, m/z 317.2111 [M + H] + and m/z 355.1670 [M + K] + for 15–oxo– ent –kaur–16–en–19–oic acid and m/z 303.2319 [M + H] + for ent –kaur–16–en–19–oic acid. The fragmentation patterns of the compounds were proposed based on the HRESI–MS n measurements. Conclusions: The study revealed the spatial variability, differential behaviours and specificity of the selected kaurane diterpenes in the fruit, seed and pericarp. The compounds under study were predominantly restricted to the pericarp of the fruit with trace amounts in the seed. Abstract : The spatial distribution of selected kaurane diterpenes in the fruit, seed and pericarp of X. aethiopica was revealed using MALDI–MS imaging techniques. The compounds were predominantly restricted to the pericarp of the fruit.